PENGEMBANGAN MASYARAKAT DALAM KEHIDUPAN SOSIAL DI HATUSUA - Fransina Matakena (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Communication in public life is needed by everyone to realize a good life with all the goals of life. Good interaction is needed by all levels of society to be able to carry out the process of adaptation to the environment in which humans are located. The success of tourism development in a place requires a good balance between various aspects of life, both economic, environmental and socio-cultural aspects. The method in this service is to provide material and understanding to people who have businesses in the Hatusua Beach area, Kairatu sub-district, Central Maluku district in interpreting the process of good interaction in society. The result of this activity is that the community has good insight in developing business through interactions that have a positive impact, thus giving a good impression for visitors to visit again with excellent service through communication and interaction so as to produce a better social life.